The Role of IL-35 in the Pathophysiological Processes of Liver Disease - Hu, Shuang; Lian, Pan-pan; Hu, Ying; Zhu, Xing-yu; Jiang, Shao-wei; Ma, Qiang; Li, Liang-yun; Yang, Jun-fa; Yang, Li; Guo, Hai-yue; Zhou, Hong; Yang, Chen-chen; et al. (Frontiers in Pharmacology, 2021)
It is known that liver diseases have several characteristics of massive lipid accumulation and lipid metabolic disorder, and are divided into inﬂammation, liver ﬁbrosis, liver cirrhosis (LC), and hepatocellular carcinoma (HCC) in patients. Interleukin (IL)-35, a new-discovered cytokine, can protect the liver from the environmental attack by increasing the ratio of Tregs (T regulatory cells) which can increase the anti-inflammatory cytokines and inhibit the proliferation of immune cellular. Also, IL-35 played crucial function in the process of liver diseases thought immunosuppressive regulation. When liver injury and inflammation occurred, two opposite mechanism, pro-inflammatory and anti-inflammatory, were in relation to the ultimate formation of diseases. Some obvious advantages indicate that IL-35 could be seen as a new therapeutic target to control the progression of liver diseases, but its mechanism of function still needs further research.